Pengaruh modal kerja, perputaran aktiva, dan leverage terhadap profitabilitas - Syahzuni, Barlia Annis; Jimmy, Jimmy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The impact of digital transformation in Indonesia on the food and beverage industry can support and facilitate activities in the industry. However, this makes the competition in the industry higher, causing the profit to decrease. The purpose of this study is to determine the impact of working capital, asset turnover and leverage on company profitability in the food and beverage industry in the Liquors, Soft Drinks, Dairy Products, Processed Foods and Fish, Meat & Poultry sub-sectors. The data source comes from the annual financial statements of companies listed on the Stock Exchange with a sampling technique using purposive sampling method in accordance with the research criteria. The research period was taken for 5 years from 2017 to 2021 with the number of sample data used as many as 135 data from 27 entities. This study utilizes multiple linear analysis methods with secondary data types. The results of the study show that working capital, asset turnover and leverage simultaneously have an effect on profitability. While working capital has a positive impact on profitability, asset turnover has no impact on profitability and leverage has a negative impact on profitability.